2014
DOI: 10.3354/esr00565
|View full text |Cite
|
Sign up to set email alerts
|

Kemp’s ridley Lepidochelys kempii nesting abundance in Texas, USA: a novel approach using genetics to improve population census

Abstract: Accurate estimates of the annual numbers of nesting females are critical for assessing sea turtle populations. Nesting by Kemp's ridley Lepidochelys kempii turtles has significantly increased at Padre Island National Seashore and nearby beaches in Texas, USA. Four nests were observed in Texas during 1995 and a record of 209 in 2012. However, it is unclear how many clutches are laid by the same females. We used a genetic approach to infer the number of individual nesters from genotypes determined from dead embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 30 publications
4
34
0
Order By: Relevance
“…We also found that sibship frequency‐based estimates of the effective number of breeders were consistent across sample years and had overlapping confidence intervals with estimates based on linkage disequilibrium, another commonly employed single‐sample N b estimator. The value of estimating counts of parents and family groups through sibship reconstruction has been demonstrated in other systems, such as monitoring abundance of social bee colonies by identifying sisters among foraging workers and estimating the number of female sea turtles (green [ Chelonia mydas ] and Kemp's ridley [ Lepidochelys kempii ] sea turtles) laying multiple clutches per season at the same nesting site (Toquenaga and Kokuvo ; Frey et al , ; Geib et al ). Fisheries and aquaculture systems have used similar methods to shed light on genetic variability between age stages, assess stocking strategies, and reconstruct putative parental genotypes among externally fertilized species (Liu and Ely , Li et al , Meraner et al , Hasanat et al ).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that sibship frequency‐based estimates of the effective number of breeders were consistent across sample years and had overlapping confidence intervals with estimates based on linkage disequilibrium, another commonly employed single‐sample N b estimator. The value of estimating counts of parents and family groups through sibship reconstruction has been demonstrated in other systems, such as monitoring abundance of social bee colonies by identifying sisters among foraging workers and estimating the number of female sea turtles (green [ Chelonia mydas ] and Kemp's ridley [ Lepidochelys kempii ] sea turtles) laying multiple clutches per season at the same nesting site (Toquenaga and Kokuvo ; Frey et al , ; Geib et al ). Fisheries and aquaculture systems have used similar methods to shed light on genetic variability between age stages, assess stocking strategies, and reconstruct putative parental genotypes among externally fertilized species (Liu and Ely , Li et al , Meraner et al , Hasanat et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Positive (a previously analysed loggerhead turtle (Caretta caretta) sample) and negative controls were also included. Sequences were aligned manually by the BioEdit programme, version 5.0.9 (Hall, 1999), and were compared with the haplotypes described for both species of the genus Lepidochelys, as found in the literature (Bowen et al, 1998;Shanker et al, 2004; López instead of Lopez-Castro & Rocha-Olivares, 2005; Reis et al, 2010;Jensen et al, 2013;Frey et al, 2014) and in the GenBank database (National Center for Biotechnology Information, USA: NCBI Home page http://www.ncbi.nlm.nih.gov) by a BLAST search. When sequences were not available in Genbank, they were extracted from the polymorphic tables found in the references that describe them.…”
Section: Methodsmentioning
confidence: 99%
“…Nest sampling may also supplement traditional tagging approaches thus improving annual censuses of nesting populations where nesting females cannot be consistently observed. For example, Frey et al (2014) used parentage analysis and genetic fingerprinting for a limited number of known Kemp's ridley mothers along with hatchlings from unidentified nests to assign mothers for every nest. They TABLE 3 | Generalized summary of marine turtle genetic/genomic research to inform future project development.…”
Section: What Reproductive Strategies and Behaviors Do Turtles Use?mentioning
confidence: 99%